Multi-paradigm simulation projects: the need for practical guidelines - Ribeiro, Marco (2014)
We are surrounded by complexity and uncertainty that constrain our ability to learn and understand the systems around us. We need tools that allow us to deal more effectively with complexity in order to be able to make better decisions. Simulation is such a tool. It provides the means to experiment and learn from observed behavior. Simulation can be used to effectively support the evaluation of complex scenarios, however its effectiveness is deeply rooted in the ability to build models that capture all the relevant details and dynamics of a complex sys-tem. Several approaches to modelling exist, however we believe that adopting a single simulation approach may prove limiting. In this paper we argue that, in more complex situations, a multi-paradigm simulation approach, in which more than one simulation paradigm is used to study the same reality, may be a better approach. The problem is that, its adoption is challenged by a tendency to use the simulation paradigm one is most familiar with and the lack of guidelines on how to choose and combine distinct simulation paradigms.